PENGUATAN KERANGKA HUKUM TERKAIT PENYELESAIAN SENGKETA PASAR MODAL SYARIAH PADA PENGADILAN AGAMA - Irawan, Mul (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2016)
According to the sharia point of view, sharia capital market is muamalah product. Capital market transactions are allowed as long as it does conflict with the terms outlined by sharia. The rapid development of Indonesia sharia capital market results in the increasing number and variety of potential legal problems. It takes two legal efforts in strengthening the legal framework for sharia capital market. First, preventive measures to minimize the legal issues occurrence, such as the establishment of islamic law regulations in order to produce stability and good atmosphere of sharia capital market law enforcement. Second, efforts in sharia capital market mediation which is done through support the religious court as the only judicial institutions having the absolute authority in resolving sharia capital market civil cases. We need to increase the judges and religious courts officials competencies, make guidelines, jurisprudence and the references of sharia capital market dispute resolution in Indonesia.Keywords: legal framework, sharia capital market, civil dispute, religious court